Polyacrylamide Grafted Gum Acacia (GA-g-PAM) Graft Copolymer as Efficient Polymeric Scaffold - Bal, Trishna; Singh, Priyashi; Rajora, Aditya Dev; Garg, Sandeep; Ghosh, Barnali Dasgupta; Pattnaik, Ashok Kumar (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Natural polysaccharides are mostly not stable in their original form but their biodegradable properties can be beneficial for use as polymeric scaffolds for tissue engineering. Microwave irradiation assisted grafting synthesis being an easy and quick method enhances stability of these natural polysaccharides. Materials and Methods: Initially the optimization of the redox initiator ammonium per sulfate (APS) along with the monomer concentration acrylamide (AM) was done by % grafting efficiency (%GE) for getting the optimized grade of graft copolymer (GA-g-PAM). The microwave time was kept constant with the concentration of the polymer Gum acacia (GA). Different analytical techniques were used for the characterization of optimized grade G6 like Fourier transform infrared spectroscopy (FTIR), Differential scanning calorimetry (DSC), X-ray diffraction(XRD) and Nuclear magnetic resonance (NMR) which confirmed successful grafting reactions and scanning electron microscopy (SEM) was utilized to analyze the interior architecture as well the cell proliferation on to the polymer surface. The optimized grade G6 was inserted under the skin hypodermis for tissue proliferation. Results: The % grafting efficiency (%GE) of optimized grade of Polyacrylamide grafted Gum acacia (GA) graft copolymer (GA-g-PAM) was 94.54%. Histolology studies of local tissue of the test mice revealed that the polymer material after insertion onto the mice skin enhanced the cell proliferation as there were evidences of more collagen as well as fibroblast growth in test animal local tissue than in comparison to control mice. Conclusion: Thus, results indicate that polyacrylamide grafted gum acacia graft copolymer (GA-g-PAM) is sufficiently biocompatible and suitable as versatile material for tissue engineering purpose.
Keywords: Graft copolymer; Microwave assisted synthesis; Tissue engineered scaffold; Gum acacia; Acrylamide